2017
DOI: 10.1161/cir.0000000000000490
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Biomarkers for the Prevention, Assessment, and Management of Heart Failure: A Scientific Statement From the American Heart Association

Abstract: Background and Purpose: Natriuretic peptides have led the way as a diagnostic and prognostic tool for the diagnosis and management of heart failure (HF). More recent evidence suggests that natriuretic peptides along with the next generation of biomarkers may provide added value to medical management, which could potentially lower risk of mortality and readmissions. The purpose of this scientific statement is to summarize the existing literature and to provide guidance for the utility of currently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
397
0
41

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 473 publications
(443 citation statements)
references
References 291 publications
(324 reference statements)
5
397
0
41
Order By: Relevance
“…High sensitivity troponin release in the absence of coronary hypoperfusion is also a marker of ongoing myocyte injury and necrosis [39][40][41][42][43]. A scientific consensus is that natriuretic peptide and high sensitivity troponins add prognostic information for predicting new-onset HF [44]. Additional promising biomarkers include a family of inflammatory mediators and oxidative stress markers, which participate in the inflammation cascade that leads to tissue injury, remodeling and fibroblast proliferation.…”
Section: Cs Distinguishes Failing Cardiac Muscle From Hf Comorbiditiesmentioning
confidence: 99%
“…High sensitivity troponin release in the absence of coronary hypoperfusion is also a marker of ongoing myocyte injury and necrosis [39][40][41][42][43]. A scientific consensus is that natriuretic peptide and high sensitivity troponins add prognostic information for predicting new-onset HF [44]. Additional promising biomarkers include a family of inflammatory mediators and oxidative stress markers, which participate in the inflammation cascade that leads to tissue injury, remodeling and fibroblast proliferation.…”
Section: Cs Distinguishes Failing Cardiac Muscle From Hf Comorbiditiesmentioning
confidence: 99%
“…Recently ended STOP-HF (The St Vincent's Screening to Prevent Heart Failure) trial [3] was reported that BNP-based screening was able to reduce the composite endpoint of asymptomatic cardiac dysfunction (regardless to systolic or diastolic) with or without newly diagnosed chronic HFrEF/HFpEF that confirms the immense role of screening NPs and early intervention may prevent HF. More recent evidence suggests that NPs along with the next generation of CV biomarkers could provide added predictive value to drug therapy of HF, which could potentially lower HF-related risk of outcomes [4,5].…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Для предсказания вероятно-сти наступления неблагоприятного сердечно-сосудис того события использовалась логистическая как функциональный класс (ФК) New York Heart Association (NYHA), фракция выброса левого желу-дочка (ФВ ЛЖ), рутинные лабораторные показатели, не могут полностью оценить риск неблагоприятных клинических исходов и определить индивидуальный прогноз у пациентов с СН. Стратификацию риска улучшает применение биомаркеров, отражающих различные механизмы формирования и развития синдрома СН [1][2][3].…”
unclassified
“…Их повышенная секреция связана с растяжением кардио-миоцитов, однако на сывороточные концентрации оказывают влияние и другие факторы, включая воз-раст, почечную функцию, анемию. Кроме того, НП раскрывают не все патогенетические аспекты СН, что актуализирует поиск новых биомаркеров, облада-ющих как дополнительным, так и самостоятельным прогностическим значением [3,6].…”
unclassified
See 1 more Smart Citation